(untitled) (Educational Knowledge, 2014)
This article presents the results of applying the CSI: DONAS didactic strategy, designed during the first semester of 2013 for the course OE-0185 Didactics of Special Education II, within the Bachelor of Science in Education program with an emphasis in Special Education at the University of Costa Rica. The strategy aimed to systematically and effectively guide the group of students in case studies. It consisted of a square matrix that outlined the steps students should follow in the diagnostic evaluation process of a student with reading and writing difficulties. This evaluation aimed to identify the student’s educational needs and determine the necessary educational support services, based on the student’s curricular competency profile. The article describes how this didactic strategy was introduced to the students and the follow-up provided throughout the semester to ensure they completed the proposed systematic process. The results of the experience were gathered in two ways: through an opinion questionnaire administered to the student group, and through the student performance record kept by the teacher throughout the academic year. The discussion analyzes the strengths and limitations of the strategy. It also highlights its relevance in subsequent academic years and even the possibility of extending it to other courses that involve case studies, given the effectiveness demonstrated in the results analysis.